Reclaiming Identity: Women, Social Exclusion, and Resistance in Bumi Manusia - Sofi, Muhammad Jauhari; Basiri, Nasim (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
This paper aims to unveil the gender-based prejudice and the colonial state's policies that systematically exclude Native women by considering Pramoedya A. Toer's Bumi Manusia. It focuses on how women are excluded from useful social life participation and resist such unfair treatment to reclaim their own identity. A close textual analysis with postcolonial and feminist discourses was used in this literary study to interpret particular feelings, experiences, and events in the novel. After a comprehensive examination, the study found that women during the Dutch occupation in Java were denied their rights, freedom, and opportunities crucial to their social integration; they had to live their lives according to the interests of the ruling classes, i.e., the men and the white Europeans. Various forms of resistance, ranging from the lowest opposition mode to open rebellions, have been articulated as a response to the said social exclusion. In this sense, the novel exposes a female character that can take on a new form of existence. The insights gained from this study might be of assistance to confirm the awakening of women's consciousness in struggling against the oppressive power of sexism and racism in early twentieth century Java.